Update on Direct Oral AntiCoagulants (DOACs) - Koscielny, J.; Rosenthal, C.; von Heymann, C. (Phlebologie, 2018)
Recent findings require an update of previous recommendations for the perioperative use of Direct Oral AntiCoagulants (DOACs). A break in preoperative treatment of 24-96 hours is recommended based on the pharmacokinetic profiles of DOACs and depends on individual patient characteristics, their renal and possibly liver function, and their surgery-related risk of bleeding. In cases of renal or hepatic insufficiency, whether to extend the preoperative interruption of IIa- and Xa-inhibitors is a clinical decision that must be reached on an individual patient basis. In cases of epidural or spinal anaesthesia, more conservative pausing-intervals are recommended due to the risk of persistent neurologic deficits (e.g., paraplegia) following the development of spinal subdural and epidural haematomas. Elective surgery should be postponed according to these recommendations. Preoperative “bridging” with LMWH (more precisely referred to as “switching”) should be omitted due to a significantly increased risk of bleeding. In addition, the incidence of perioperative thromboembolic risks, such as DVT, PE, and stroke, are no different whether interruption or „switching” is undertaken. Postoperatively, the DOACs can be reinstituted within the first 24 hours. In cases of major surgery or if there is a higher risk of bleeding, resumption of DOACS should only begin after 24-72 hours. In patients with an elevated thromboembolic risk, transient postoperative LMWH administration can be recommended during this period.Interaction of DOACs with other drugs usually occurs during the absorption, transport and elimination of these drugs. Therefore, substance-specific restrictions and recommendations should be observed during these times. In everyday clinical practice, webbased, independent information portals on drug-interactions are very helpful in providing safe and rapid information about potential interactions when DOACs are used in combination with other drugs, especially during perioperative management.Non-adherence to medications is a worldwide problem that has dangerous and costly consequences. Present data suggest that persistence is the primary factor that supports adherence. Despite the adherence data presented in the DOACS approval studies (e.g., persistence in the treatment of acute venous thromboembolism has been reported to be between 94-99%), the first registries and meta-analyses provide sobering results regarding the incidence of persistence and the success rate of interventions designed to improve adherence with DOACs in cases of long-term usage.Nachdruck aus und zu zitieren als: Hämostaseologie 2017; 37: 267–275 https://doi.org/10.5482/HAMO-16-10-1657856
Keywords: DOACs; rivaroxaban; apixaban; edoxaban; dabigatran; “switching”; drug interactions; persistence